Association between genetic risk and adherence to the Dietary Approaches to Stop Hypertension diet for developing venous thromboembolism - Li, Si; Jiang, Minghui; Guan, Yunlong; Cao, Xi; Shao, Zhonghe; Deng, Jun; Hao, Xingjie (Research and practice in thrombosis and haemostasis, 2025)
The relationship between diet and venous thromboembolism (VTE) remains unclear, and the joint effects of diet patterns and genetic susceptibility on VTE risk are unknown. Investigate the independent and joint effects of Dietary Approaches to Stop Hypertension (DASH) diet adherence and polygenic risk scores (PRS) on VTE risk. A total of 411,539 UK Biobank participants were included. DASH scores were calculated using Food Frequency Questionnaires, and PRS quantified genetic risk. Cox proportional hazard models estimated hazard ratios (HRs) for VTE, assessing interactions between the DASH diet and genetic susceptibility. During a median follow-up of 13.4 years, 10,543 participants were diagnosed with VTE. Higher DASH scores were associated with a lower VTE risk (HR, 0.87; 95% CI, 0.82-0.92). A low-adherent DASH diet combined with high-genetic risk had the highest VTE risk (HR, 2.78; 95% CI, 2.47-3.14). High DASH scores reduced VTE risk in high-genetic-risk individuals (HR, 0.84; 95% CI, 0.76-0.92). Sex-specific associations were detected in the joint effect and interaction of DASH scores and PRS. Notably, high DASH scores can offset moderate genetic risk among men (HR, 0.79; 95% CI, 0.67-0.94). There were additive interactions between DASH scores and high genetic risk in total subjects and men, while not observed in women. The DASH diet is associated with reduced VTE risk and can partially offset genetic predisposition. Low adherence to the DASH diet increases VTE risk, particularly in high-genetic-risk individuals. The protective effect of high DASH scores against genetic risks for VTE is more pronounced in males. Precision medicine should consider both diet and genetics for VTE prevention. [Display omitted] •Diet and genetic risk interaction on VTE remains unclear.•We analyzed 411,539 UK Biobank participants.•The DASH diet lowered VTE risk despite high genetic risk.•We found an additive DASH diet–genetic risk interaction in all subjects and men.